#TITLE_ALTERNATIVE# - ARIEF NARENDRA (NIM : 10213023), HASTO
Ionizing radiation for cancer treatment also known as radiotherapy has undergone development for more than century. Radiation kills cancer by giving partially or entirely all of the energy to the tumour tissue, especially in the DNA. If a tumour or a cancer is irradiated by radiotherapy, there is no way to avoid the tissue near the cancer will be affected by the radiation. As a result, the healthy tissue near tumour will loss their functionality, or worse, there may appear the new tumour in that tissue. Therefore, it should be done some improvement in quality of radiotherapy, one of the example is optimization of time-dose fractionation radiotherapy scheme. To optimize the fractionation dose, it is made a program in matlab using simulated annealing as optimization method. The objective function is Biologically Effective Dose of the cancer, with Biologically Effective Dose of the healthy tissue around the cancer as a constraint. After obtaining the optimum dose per fraction, then the data will be analyzed toward the total and fractionation time. Thus, it would be obtained the optimum of time scheme and dose fractionation of a cancer. The result of this research will show the dose per fraction from total time in 10 until 60 days from both of the treatment scheme, the value of Biologically Effective Dose of the cancer, and the optimum of dose per fraction from both of the treatment.